Mental foramen: A predictor of age and gender and guide for various procedures - Vijay K Asrani; Jigna S Shah (Wolters Kluwer Medknow Publications, 2018)
Background: The distance from the inferior border of mental foramen (MF) to lower border of mandible remains constant throughout the life. Considering this fact the present study was carried out to determine role of MF in age and gender estimation and also its importance in planning various treatments. Aims and Objective: (1) To determine the most common type and shape of MF 2) To measure the height of the mandibular body (H), the distance between the superior margin of the MF to the alveolar crest (SM-AC), the distance between the superior margin of the MF to the inferior border of the mandible (SM-IB), the distance between the inferior margin of the MF to the inferior border (IM-IB) on the right side and left side. (3) To compare the above measurements for age and gender determination. (4) To determine effect of various factors on above measurements (5) to evaluate whether any significant difference in measurement occurs on right and left side. (6) To derive a regression equation for age estimation. Materials and Methods: A total of 300 Orthopantomogram were studied. Measurements such as H, SM-AC, SM-IB and IM-IB were carried out on both sides on type II MF in males and females in all the six age groups. Statistical analysis was carried using IBM SPSS version 24 to determine differences in measurements and linear regression analysis was carried out to determine age of individuals. Result: The most common appearance of MF was type II and shape was oval. Statistically significant differences occurred in measurements using which regressive equation for age estimation was derived for males & females. Conclusion: MF, being a stable landmark in mandible, serves as a good indicator for the determination of age and gender. Hence, using certain measurements related to MF, it can help in determining the age of the individual. Further, its position and distance from the alveolar crest serve as a guide for orthognathic surgeries, implant placement, and pre-prosthetic surgery.